1983
DOI: 10.1128/aem.46.3.738-748.1983
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacterial and fungal degradation of Digitaria pentzii grown with or without sulfur

Abstract: Sheep fed the forage Digitaria pentzii fertilized with sulfur were compared with those fed unfertilized forage for the rumen microbial population involved with fiber degradation. No differences were detected in the bacterial population as determined by anaerobic cultures on a habitat-simulating medium, xylan, or pectin, by 35S labeling techniques for microbial protein, or by transmission electron microscopic studies of bacterium-fiber interactions. Rumen volume and water flow from the rumen were not different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(51 citation statements)
references
References 33 publications
(32 reference statements)
2
49
0
Order By: Relevance
“…36 They are responsible for most of the plant cell wall degradation in the rumen ecosystem, where they seem to interact with rumen bacteria. 19,45,100 As pointed out above, individual enzymes from anaerobic fungi isolated or obtained by cloning generally have higher specific activities than similar enzymes from other sources. These properties seem to be of value when considering enzymes from anaerobic fungi for industrial uses, which may involve the bioconversion of lignocellulose to sugars fermentable to ethanol for fuel or the production of other industrial feed stock chemicals.…”
Section: Orpinomyces Enzymes-some Applied Workmentioning
confidence: 93%
See 2 more Smart Citations
“…36 They are responsible for most of the plant cell wall degradation in the rumen ecosystem, where they seem to interact with rumen bacteria. 19,45,100 As pointed out above, individual enzymes from anaerobic fungi isolated or obtained by cloning generally have higher specific activities than similar enzymes from other sources. These properties seem to be of value when considering enzymes from anaerobic fungi for industrial uses, which may involve the bioconversion of lignocellulose to sugars fermentable to ethanol for fuel or the production of other industrial feed stock chemicals.…”
Section: Orpinomyces Enzymes-some Applied Workmentioning
confidence: 93%
“…In addition, accessory enzymes were found for hemicellulose degradation, including acetyl xylan esterase, feruloyl-and p-coumaroyl esterases, and α-(4-O-methyl)-glucoronidase. 19,20 Two feruloyl esterases (FAE-I and FAE-II), and one p-coumaroyl esterase (CAE) have been purified from culture media of Neocallimastix strain MC-2. 78,79 These esterases function synergetically together with commercial xylanase preparations from Trichoderma viride (Sigma-Aldrich Corp., St. Louis, MO) and Basidiomycetes (Driselase; Sigma).…”
Section: Hemicellulases and Associated Enzymes From Orpinomyces Pc-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ¢rst anaerobic fungus, Neocallimastix frontalis, was isolated in 1975 from the rumen of sheep [1], at least 17 di¡erent anaerobic fungi have been isolated from ruminant and nonruminant herbivores. Anaerobic fungi produce highly active hydrolytic enzymes [2], they physically associate with the lignocellulosic tissue of plant fragments, and their hyphae penetrate the plant tissue in vivo [3,4], indicating that they are involved in degradation of plant biomass and play an important role in the rumen ecosystem. Several genes coding for hydrolytic enzymes have been cloned and sequenced from the monocentric fungi Neocallimastix patriciarum [5^9], N. frontalis [10,11], and Piromyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…Since Orpin [1,2] found that several flagellated protozoa in the rumen were in fact the zoospore stages of strictly anaerobic phycomycetous fungi, studies have been directed towards establishing the importance of these fungi in the rumen. Light and electron microscopy have shown that the fungi are attached to plant material [3][4][5] and it has been suggested that they play a role in degrading [5] and weakening plant fibre [6].…”
Section: Introductionmentioning
confidence: 99%